Advanced Ni-Nio coatings for enhanced corrosion inhibition of mild steel in alkaline concrete environments: an integrated experimental and computational analysis - Suhas, V. S.; Shanmugapriya, T. (Frontiers in Built Environment, 2025)
This study investigates advanced Ni–NiO coatings for improving the corrosion protection of mild steel in alkaline concrete environments using an integrated experimental and computational approach. Mild steel samples were coated with Ni–NiO, both as duplex coatings and in combination with epoxy and PVDF binders, and their corrosion resistance was evaluated. Electrochemical methods, such as Tafel analysis and electrochemical impedance spectroscopy (EIS), were employed to assess the corrosion performance over a 28-day exposure period. COMSOL Multiphysics simulations were conducted by modelling key parameters, including the geometry of the steel-concrete system, the mechanical properties of steel, concrete, and corrosion products, as well as the diffusion coefficients of Fe2+ and Fe3+ ions, corrosion current density, porosity, and coating thicknesses. These simulations accurately replicated the progressive corrosion-induced damage and ion transport phenomena observed experimentally, enabling a direct comparison with experimental results. The Ni–NiO duplex system demonstrated higher corrosion resistance compared to other coated samples, which consistently exhibited the lowest corrosion rates, highest impedance, and most stable corrosion potentials throughout the study period. The enhanced performance of the duplex coatings was attributed to the formation of a dense, chemically stable barrier and the synergistic effects of the oxide layers and zincate pretreatment, as validated by both computational modelling and electrochemical data. This combined experimental and computational investigation demonstrates the significant potential of Ni–NiO duplex coatings for the long-term protection of steel reinforcements in concrete structures.